Echocardiographic assessment of inappropriate left ventricular mass and left ventricular hypertrophy in patients with diastolic dysfunction - Hasan Shemirani; Rohola Hemmati; Alireza Khosravi; Mojgan Gharipour; Mahnaz Jozan (Journal of Research in Medical Sciences, 2012)
Background: early diagnosis of left ventricular mass (LVM) inappropriateness and left ventricular hypertrophy (LVH) can result in preventing diastolic left ventricular dysfunction and its related morbidity and mortality. This study was performed to determine if diastolic dysfunction is associated with LVH and inappropriate LVM. Materials and Methods: one hundred and twenty five uncomplicated hypertension from Isfahan Healthy Heart Program underwent two-dimensional echocardiography. Inappropriate LVM was defined as an LVM index greater than 88 g/m2 of body-surface area in women and greater than 102 g/m2 in men. LVH-defined septal and posterior wall thickness greater than 0/9 cm in women and greater than 1 cm in men, respectively. Echocardiographic parameters, including early diastolic peak velocity (E)/late diastolic peak velocity (A), deceleration time (DT), and E/early mitral annulus velocity (E′) were measured. Results: the mean systolic and diastolic blood pressure at the patients′ admission day were 142.87 ± 18.12 and 88.45 ± 9.18 mmHg, respectively. Totally, 21.7% of subjects had inappropriate LV mass that moderate and severe abnormal LV mass was revealed in 5.6% and 5.6%, respectively. The mean of age and BMI was significantly higher in patients with moderate left ventricular hypertrophy (P < 0.05). Adjusted by age, gender, BMI, and systolic and diastolic blood pressures, both E/A ratio and deceleration time were higher in those with the severer ventricular hypertrophy. Subjects with severe showed significantly higher BMI 33. 7 ± 3.7 (P < 0.001). There was a slight difference between the grade of diastolic dysfunction and the severity of inappropriate LV mass (P = 0.065). But no significant difference was found between E/A, E/E′, and deceleration time and the level of inappropriate LV mass (P > 0.05). Spearman′s Rank test was used to test the correlation between diastolic dysfunction and LV mass (P = 0.025). Conclusion: LVH is correlated with the severity of diastolic dysfunction manifested by the E/A value and deceleration time, but inappropriate LVM can slightly predict diastolic dysfunction severity in uncomplicated hypertension.